Alternative Sigma Factor B in Bovine Mastitis-Causing Staphylococcus aureus: Characterization of Its Role in Biofilm Formation, Resistance to Hydrogen Peroxide Stress, Regulon Members - Sirirak Supa-amornkul (2020)
© Copyright © 2019 Supa-amornkul, Mongkolsuk, Summpunn, Chaiyakunvat, Navaratdusit, Jiarpinitnun and Chaturongakul. This study examines treatments of the bacterial pathogen Staphylococcus aureus, namely, in the context of its being a major cause of subclinical bovine mastitis. Such infections caused by S. aureus among dairy cows are difficult to detect and can easily become chronic, leading to reduced productivity and large losses for dairy manufacturers. In this study, the role of alternative sigma factor B (σB), which has been shown to be a global regulator for S. aureus infections, was explored in a mastitis-causing S. aureus strain, RF122. For comparison with the wild-type strain, a sigB null (ΔsigB) mutant was constructed and analyzed for its phenotypes and transcriptome. Our study found that σB is essential for biofilm formation as the ΔsigB mutant strain produced significantly less biofilm than did the wild-type strain at 48 h. σB is involved in response to H2O2 stress. However, σB plays a minor or no role in resistance to antiseptics (e.g., povidone-iodine and chlorhexidine), resistance to tested antibiotics, hemolysin activity, and invasion ability. RNA sequencing identified 225 σB-dependent genes, of which 171 are positively regulated and 54 are negatively regulated. The identified genes are involved in stress response, pathogenesis, and metabolic mechanisms. Quantitative TaqMan RT-PCR was performed to verify the RNA sequencing results; i.e., σB is a positive regulator for asp23, sarA, katA, yabJ, sodA, SAB2006c, and nrdD expressions. In the RF122 strain, σB plays a role in biofilm formation, general stress response (e.g., H2O2), and regulation of virulence factors and virulence-associated genes.